Genome-wide association mapping for phenotypic plasticity in rice - Kikuchi, Shinji; Bheemanahalli, Raju; Jagadish, Krishna S.V.; Kumagai, Etsushi; Masuya, Yusuke; Kuroda, Eiki; Raghavan, Chitra; Dingkuhn, Michael; Abe, Akira; Shimono, Hiroyuki (Wiley, 2017)
Phenotypic plasticity of plants in response to environmental changes is important for adapting to changing climate. Less attention has been paid to exploring the advantages of phenotypic plasticity in resource‐rich environments to enhance the productivity of agricultural crops. Here, we examined genetic variation for phenotypic plasticity in indica rice (Oryza sativa L.) across two diverse panels: (1) a Phenomics of Rice Adaptation and Yield (PRAY) population comprising 301 accessions; and (2) a Multi‐parent Advanced Generation Inter‐Cross (MAGIC) indica population comprising 151 accessions. Altered planting density was used as a proxy for elevated atmospheric CO2 response. Low planting density significantly increased panicle weight per plant compared with normal density, and the magnitude of the increase ranged from 1.10 to 2.78 times among accessions for the PRAY population and from 1.05 to 2.45 times for the MAGIC population. Genome‐wide‐association studies validate three Environmental Responsiveness (ER) candidate alleles (qER1–3) that were associated with relative response of panicle weight to low density. Two of these alleles were tested in 13 genotypes to clarify their biomass responses during vegetative growth under elevated CO2 in Japan. Our study provides evidence for polymorphisms that control rice phenotypic plasticity in environments that are rich in resources such as light and CO2.